IBPGR: International Board for Plant Genetic Resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The International Board for Plant Genetic Resources (IBPGR) is an international scientific-organization under the aegis of the Consultative Group on International Agricultural Research (CGIAR) and established by them in 1974. The basic function of...